Stewart-treves syndrome in the lower limb after arthroplasty- A case report - Ishan Agrawal; Arunima Ray; Bikash R Kar; Ira Agrawal (Wolters Kluwer Medknow Publications, 2022)
Stewart-Treves Syndrome is a rare and fatal condition where cutaneous angiosarcoma-a high-grade malignant tumor originating in the vascular and lymphatic endothelium-classically develops in the upper limbs post-mastectomy, with radiation therapy and axillary lymph node dissection. There are very few reports of the syndrome developing in the lower limbs, without any preceding malignancy or radiation therapy. The median development time is 11 years. Angiosarcoma originates in the vascular and lymphatic vessels, and the diagnosis is based on histopathology and immunohistochemistry findings. We report an unusual presentation of the Stewart-Treves Syndrome in an elderly female involving the lower limb with preexisting chronic lymphedema, where the tumor developed 15 months after total knee arthroplasty.